1983
DOI: 10.1002/bbpc.19830871209
|View full text |Cite
|
Sign up to set email alerts
|

Small Angle Neutron Scattering Studies on Viscoelastic Detergents

Abstract: Small angle neutron scattering experiments (SANS) on solutions of cetylpyridiniumsalicylate (CPS) in D2O over a large concentration range show a characteristic scattering maximum due to mutual interactions between the rodlike micelles. From the scattering rates structure factors S(Q), pair correlation functions g(r) and corresponding mean potentials W(r) are derived. Furthermore it is shown, that the length L of the scatterers decreases in a concentration range from 20 mM to 160 mM CPS. To study the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 22 publications
3
30
0
Order By: Relevance
“…The rheological properties of the oil-like phases of ASTP-A are very peculiar; it is obviously viscoelastic and trimethylammonium bromide-salicylic acid (CTAB-SA) are interpreted in terms of a network of overlapping rodlike negative thixotropic although its viscosity is low. Table 4 shows the apparent viscosity of the oil-like phase of ASTP-micelles (16)(17)(18). Therefore, we suggested that the upper phases of ASTP-C and the water-like phases of ASTP-A A, which shows that the solution is negative thixotropic.…”
Section: The Surface Tension Of Astp Systems (25њc)mentioning
confidence: 90%
“…The rheological properties of the oil-like phases of ASTP-A are very peculiar; it is obviously viscoelastic and trimethylammonium bromide-salicylic acid (CTAB-SA) are interpreted in terms of a network of overlapping rodlike negative thixotropic although its viscosity is low. Table 4 shows the apparent viscosity of the oil-like phase of ASTP-micelles (16)(17)(18). Therefore, we suggested that the upper phases of ASTP-C and the water-like phases of ASTP-A A, which shows that the solution is negative thixotropic.…”
Section: The Surface Tension Of Astp Systems (25њc)mentioning
confidence: 90%
“…of CPS in D20 at 298 K is 0"15 mM. Hoffmann, Kalus, Thurn & Ibel (1983) observed that the rod length of micelles continues to increase for CPS concentration c (mM) from the c.m.c, up to about c*= 10 mM, at which concentration the rod length begins to be equal to the interparticle spacing. We shall call c* the overlap concentration.…”
Section: D= 2-1/2( 4000 H/n A[sds]) 1/3 X 10 S/~mentioning
confidence: 92%
“…SANS intensity distributions of these saltfree micellar solutions show a strong correlation peak which indicates a high degree of nearest-neighbour ordering of the rods. Furthermore, by addition of NaC1 (0.5-32 mM) to a 5 mM solution of CPS, L can be increased to several thousand fingstr6m (Hoffmann, Kalus, Thurn & Ibel, 1983). In a brief report Hayter & Penfold (1984) described a SANS experiment with a mixed surfactant system SDS/TDPS (tetradecylpyridinium salicylate) in aqueous solutions.…”
Section: Correlation In Ionic Micellar Solutions Subject To Shear Alimentioning
confidence: 99%
“…(12) which converges for nonzero a. Equations (l), (7) and (15) lead to an anomalous growth law [13] (n + 1) log L = constant + ~/KQ (16) The effect of counterions condensing nonuniformly is remarkable: it changes the sign of eq. (10). This comes about because the effective elec-trostatic potential does not change along the understand.…”
Section: Nonuniform Counterion Condensationmentioning
confidence: 99%